Assessing willingness of coastal communities to participate in coastal resources management in Padada, Davao del Sur, Philippines - Ecoben, David William D.; Gomez, Aurelia Luzviminda V.; Aguinaldo, Roxanne T.; Montiflor, Marilou O. (2019)
Coastal resources worldwide are at risk due to pollution, illegal fishing practices, weak policy implementation, among others. Degradation of coastal resources does not only negatively impact biodiversity, it impacts coastal communities as well. Coastal resource management (CRM) aims to address these issues in coastal areas. Literature reviews identified community participation in coastal conservation as one of the major factors towards successful CRM. This study aimed to assess the factors that induce the willingness of coastal communities to be involved in CRM efforts in Padada, Davao del Sur, Philippines. Raw data were analyzed through binary logistic regression. The data was collected from 100 households in the coastal areas of Padada. Results showed that coastal communities were willing to participate in CRM efforts. They were also more likely to participate in coastal management efforts if they rely on fishing and had children. In contrast, respondents who were married and older were less likely to participate in coastal restoration efforts. The respondents also perceived a decline in the condition of coastal re4sources caused by illegal fishing practices, pollution, among others. Local ordinances concerning costal conservation were present in Padada, and the respondents perceived that the implementation of these ordinances is effective. Policy awareness increased the likelihood of participation, especially if policy information came from national government agencies (NGAs). It was recommended that the local government of Padada, coastal communities, NGAs, the academe, and other stakeholders could also develop strategies that aim to improve policy awareness.
Keywords: Mindanao studies; Coastal resource managemet